(Collective) Memory of Racial Violence and the Social Construction of the Hispanic Category among Houston Hispanics. Issue 3 (July 2015) - Korver-Glenn, Elizabeth
Prior U.S.-based research examining the collective remembrance of racially charged events has focused on the black-white binary, largely bypassing such remembrance among U.S. Hispanics. In this article, I ask how a group of Mexican-origin Hispanics in an historic Houston barrio remember two racially charged events as well as whether and how these events are publicly commemorated. Additionally, race and collective memory research has often highlighted the role of collective memory in shaping race relations. I argue that collective memory can also be an institution, structuring macro- and micro-level representations of race. Thus, I ask whether and how respondents' memories shape the social construction of the Hispanic category. I find strong memory convergence with respect to one event—the case of Jose Campos Torres—and divergence in three directions with respect to the Moody Park riot. The former corresponds to a collective understanding of what Hispanic meant in the past while the latter corresponds to a fractured understanding of what Hispanic means in the present. I also explore how respondents' racial self-perceptions coincide with their various interpretations of the riot. Overall, I theorize that a fractured collective memory of a racially charged event suggests a fractured collective identity and contributes to an ambiguous Hispanic category. I conclude by discussing suggestions for future research.